RASIONALITAS PENGOBATAN PASIEN STROKE RAWAT INAP DI RUMAH SAKIT UMUM DAERAH DR. SOEDARSO PONTIANAK - Annafiatuzakiah, Annafiatuzakiah; Ya’ Julchairi (Journal of Innovation Research and Knowledge, 2025)
Stroke is a focal or global acute functional disorders of the brain because the blocked of blood circulation to brain. WHO study showed that the incidence of stroke varies between 48 to 240 per 10,000 per year in the population aged 45 to 54 years. This study was aimed to determine the percentage of treatment rationality of stroke patients in RSUD dr. Soedarso Pontianak which includes the right indication, right drug, right dose and the right usage based on the guidelines of stroke. This study was cross-sectional observational study using retrospective data such as medical records of hospitalized stroke patients. The total of sample for this research were 40 people. The results of patient characteristics were dominated by the male gender (52.5%); the age for men patients: >60 years (27.5%) and for women patients: 46-60 years old (25%) and men patients without a job (27.5%) and women patients without a job (45%). Clinical characteristics of treatment were dominated by patients with hypertension systolic blood pressure category (80%) and hypertension diastolic blood pressure category (70%); symptoms with loss of consciousness (31%); the comorbidity of stroke with hypertension (62.5%); type of stroke with ischemic stroke (70%); length of therapy for 1-10 days (72.5%) and patients with return state after therapy (100%). The therapy rasionality of hospitalized stroke patients in this research were 100% right indication, 100% right drug, 82% right dose and 97.5% right usage. In general, the rationality of treatment for stroke patients were 62.5%.